Implementation of Anti-Corruption Meaning in Development of Campus Bureaucracy STIHP Pelopor Bangsa - Supriyadi Supriyadi (LEGAL BRIEF, 2021)
As one of the crimes that has greatly affected human life, acts of corruption should actually be immediately abolished from various government agencies and institutions in Indonesia. corruption in the country. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that anti-corruption education is indeed an alternative that is being implemented by the government in various educational environments in Indonesia, as we know that the educational environment is one of the places that This is the most strategic strategy in an effort to convey various materials about the dangers of corruption for the next generation of the nation, for that there is a need for proper and comprehensive integration in efforts to instill anti-corruption education within the university environment, besides that universities are also known as one of the educational institutions that often print the young generation who are superior, creative and innovative, by having various briefings and knowledge about the dangers of corruption for the progress of the nation and state, it is hoped that the university environment can become the main fortress in eradicating corruption in the country.